Plasticity of photosynthetic performance of the Indian tree Butea monosperma TAUB. at three sites with different microclimates - Mikosch-Wersching, Melanie (Photosynthesis research, 2012)
The Fabaceae tree Butea monosperma (TAUB.; syn. Erythrina monosperma (LAM.)) is widely distributed in Central and West-India. We studied it at three sites, i.e. at two locations with contrasting exposure (NE and SW, respectively) in a small mountain range with poor soil on highly drained rocky slopes and at a third location in a plane with deeper soils and better water supply. The two mountain range sites differed in the light climate where the NE-slope obtained more day-integrated irradiance. Chlorophyll fluorescence was measured with a portable fluorometer and leaf samples for stable isotope analyses (δ13C, δ15N, δ18O) were collected. No differences were seen in carbon and nitrogen contents of leaves at the three sites. N and O isotope signatures of the leaves were similar at the two rocky hill slope sites. More positive values for both signatures were obtained in the leaves in the plane. For all sites saturation of ETR was only achieved well above a PPFD of 1,000 μmol m−2 s−1 indicating that the leaves were sun-type leaves. The photosynthetic performance of Butea at the plane was very similar to that at the SW-slope of the mountain range and higher ETRs were obtained at the NE-slope. Ecophysiological flexibility allows Butea to perform well in a variety of habitats and yet gives it particular fitness at specific sites. The best performance was observed in the highly insolated steep rocky hill site (NE-slope) underlining the suitability of the tree for reforestation.